2020
DOI: 10.1186/s13104-020-05188-x
|View full text |Cite
|
Sign up to set email alerts
|

The role of CA-125, GLS and FASN in predicting cytoreduction for epithelial ovarian cancers

Abstract: Objective: Cytoreduction has an important role in improving the survival rate of epithelial ovarian cancer (EOC) patients. This study aimed to assess the ability of preoperative serum CA125, FASN and GLS as predictors of cytoreductive surgery for epithelial ovarian cancer (EOC). Results: The average values of serum CA-125, FASN, and GLS in the suboptimal cytoreduction group were higher than those in optimal cytoreduction group. The cut off point (COP) was 248.55 (p = 0.0001) with 73.2% sensitivity and 73.6% sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…It is hoped that this combination can help doctors provide better therapy. 4 In conclusion, we agree that the shortening of APTT and TT related to CA125 shows the importance of early detection of coagulation parameters in patients with elevated CA125 levels to determine hypercoagulability and prevent thrombi in adenomyosis. 1 However, several studies have found that CA-125 is not a strong enough predictor if stands alone in diagnostic screening, but it requires a combination of several biomarkers which also play a role in predicting and preventing thrombosis, therefore it is necessary to carry out further research with larger samples so that the results of this research will continue to develop.…”
supporting
confidence: 70%
“…It is hoped that this combination can help doctors provide better therapy. 4 In conclusion, we agree that the shortening of APTT and TT related to CA125 shows the importance of early detection of coagulation parameters in patients with elevated CA125 levels to determine hypercoagulability and prevent thrombi in adenomyosis. 1 However, several studies have found that CA-125 is not a strong enough predictor if stands alone in diagnostic screening, but it requires a combination of several biomarkers which also play a role in predicting and preventing thrombosis, therefore it is necessary to carry out further research with larger samples so that the results of this research will continue to develop.…”
supporting
confidence: 70%
“…Furthermore, another study that specifically investigated the role of GLS in predicting optimal cytoreductive surgery in patients with EOC identified a cutoff point of 22.895. 15 Tumor growth is accompanied by distinct metabolic changes. The increased proliferation of tumor cells requires an alteration in metabolic functions to support their division.…”
Section: Discussionmentioning
confidence: 99%
“…This cutoff point was determined to be 18.32. Furthermore, another study that specifically investigated the role of GLS in predicting optimal cytoreductive surgery in patients with EOC identified a cutoff point of 22.895 15 …”
Section: Discussionmentioning
confidence: 99%